1985
DOI: 10.1007/bf00543331
|View full text |Cite
|
Sign up to set email alerts
|

Elimination kinetics of thiopentone in mothers and their newborn infants

Abstract: The elimination kinetics of thiopentone was studied in 7 newborns delivered by Caesarean section and in their mothers who had received the drug for induction of anaesthesia. At delivery, 4-9 min after induction, drug concentrations in cord blood were half those in material blood. The mean half-life of thiopentone in the newborns was about double that in their mothers (15 vs 7 h) confirming a disposition similar to other barbiturates. For the first time renal clearance of thiopentone was estimated in the newbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…marked, minute, and nil for Me-N( l), Me-N(3), and Me-N(7), resp.). Electronic and intermolecular H-bonding effects were postulated [7]. While such effects may be operative in the compounds studied here, their contribution is partial at best.…”
Section: Determination Of Log Kt Values By Rp-hplcmentioning
confidence: 97%
See 2 more Smart Citations
“…marked, minute, and nil for Me-N( l), Me-N(3), and Me-N(7), resp.). Electronic and intermolecular H-bonding effects were postulated [7]. While such effects may be operative in the compounds studied here, their contribution is partial at best.…”
Section: Determination Of Log Kt Values By Rp-hplcmentioning
confidence: 97%
“…Gaspari and Bonati [7] have shown that in N-methylated xanthines, the three Me groups make different contributions to the lipophilicity of the molecule (i.e. marked, minute, and nil for Me-N( l), Me-N(3), and Me-N(7), resp.).…”
Section: Determination Of Log Kt Values By Rp-hplcmentioning
confidence: 98%
See 1 more Smart Citation
“…In this context, it is of interest to note that Gaspari and Bonati [30] have recently shown that in methylated xanthines the lipophilic contribution of N-methyl groups as compared to NH groups is highly position-dependent ; while CH,-N( 1) markedly contributes to lipophilicity, CH,-N(3) and CH,-N(7) have little or no effect. These authors also found that the additivity rule applied only to the 1,7-dimethylation pattern, a result in keeping with the isotope effect in (l,7-dimethyl-2H,)caffeine.…”
Section: Woupmentioning
confidence: 98%
“…These authors also found that the additivity rule applied only to the 1,7-dimethylation pattern, a result in keeping with the isotope effect in (l,7-dimethyl-2H,)caffeine. Steric and electronic effects were postulated to account for these differences [30] (see Discussion).…”
Section: Woupmentioning
confidence: 99%